Frost destroys Kenyan tea - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
More than 4000 ha of tea crops were destroyed by frost in Kenya early in 2000. Small-scale tea growers also reported lost crops and a dozen processing plants had to be closed down indefinitely. Kenya is the world s fourth tea producer after China,...